Effectiveness of a brief positive skills intervention to improve psychological adjustment in patients with end-stage kidney disease newly initiated on haemodialysis : protocol for a randomised controlled trial (HED-Start) - Griva, Konstadina (2021)
Introduction Initiation onto haemodialysis is a critical transition that entails multiple psychosocial and behavioural demands that can compound mental health burden. Interventions guided by self-management and cognitive-behavioural therapy to improve distress have been variably effective yet are resource-intensive or delivered reactively. Interventions with a focus on positive affect for patients with end-stage kidney disease are lacking. This study will seek (1) to develop a positive life skills intervention (HED-Start) combining evidence and stakeholder/user involvement and (2) evaluate the effectiveness of HED-Start to facilitate positive life skills acquisition and improve symptoms of distress and adjustment in incident haemodialysis patients. Methods and analysis This is a single/assessor-blinded randomised controlled trial (RCT) to compare HED-Start to usual care. In designing HED-Start, semistructured interviews, a codesign workshop and an internal pilot will be undertaken, followed by a two-arm parallel RCT to evaluate the effectiveness of HED-Start. A total of 148 incident HD patients will be randomised using a 1:2 ratio into usual care versus HED-Start to be delivered in groups by trained facilitators between January 2021 and September 2022. Anxiety and depression will be the primary outcomes; secondary outcomes will be positive and negative affect, quality of life, illness perceptions, self-efficacy, self-management skills, benefit finding and resilience. Assessments will be taken at 2 weeks prerandomisation (baseline) and 3 months postrandomisation (2 weeks post-HED-Start completion). Primary analyses will use an intention-to-treat approach and compare changes in outcomes from baseline to follow-up relative to the control group using mixed-effect models. Ethics and dissemination Ethics approval was obtained from Nanyang Technological University Institutional Review Board (IRB-2019-01-010). Written informed consent will be obtained before any research activities. Trial results will be disseminated via publications in peer-reviewed journals and conference presentations and will inform revision(s) in renal health services to support the transition of new patients to haemodialysis. Trial registration number NCT04774770.